Global agricultural trade architecture: contemporary triggers - E. N. Smirnov; E. A. Karelina; M. G. Pletnev (Вестник университета)
The key changes observed in modern international trade in agricultural products have been analyzed from the position of assessing the challenges faced by agricultural markets in recent years. The features of the agro-industrial products international trade evolution have been considered, the main trends and changes in global production and consumption have been assessed, and medium-term development prospects have been deﬁned. The world land fund transformation due to international trade development, which has become signiﬁcantly diversiﬁed, has been shown, and the preservation of differentiation among net exporters and net importers of agricultural products has been noted. The changes in the world production and consumption of agricultural commodities formulated in the course of the study have become the key trigger for modernization of the global architecture of international trade. It has been shown that it will remain a key factor in the further development of agricultural production, but the process achieved in exports and imports liberalization is signiﬁcant in terms of ensuring food security of the least developed importing countries. It has also been found that world agricultural commodity prices will stabilize in the medium term, which is an important factor in the food security of developing countries.